A Study on Structural Patterns of Trap Systems in K Field, Taranaki Basin, New Zealand - Zainudin, Qistina (2016)
The purpose of this study is to investigate the evolution of structural patterns and model the structural patterns of an existing trap systems in a specific interval of K field, Taranaki Basin, New Zealand which might lead to other new possible prospect identification. The study area is a producing field with 410 km2 3D seismic data.